Robert Nozick’s Minimal State: A Critique - Augustine Terhide Maashin (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2022)
The book, Anarchy, State and Utopia by Robert Nozick’s is his most celebrated work in which the author discusses his political thoughts. His theory of Justice (The Entitlement Theory) and the Minimal State constitute the major themes in this book. Against John Rawl’s theory of justice which is distributive in nature, Nozick develops his theory of justice which he terms “entitlement theory”,a theory thatplaces emphasis on actual consent rather than rationality as the basis of political control which is actualized in the minimal state. For Nozick, the minimal state is the only morally justifiable form of government. This contention rests upon his understanding of the separateness of each person, the existence of inviolable rights, and the side constraint that these rights impose on the behaviour of others. Nozick claims that persons are rational, they are moral agents, and they have free will. In addition, they have the ability to regulate and guide their lives in accordance with some overall conception of their choice. His advocacy of a minimalist state limited to the protection of the people against theft, fraud and the enforcement of contract, his emphasis on the exclusive right to own property, rejection of coercive taxation, rejection of the provision of public social amenities amongst others is flawed and constitutes a problem in this regard. This paper concludes that, the kind of state envisaged by Nozick is utopia. However the good elements of his theory can be modified to make for the kind of state that prioritizes individual rights.